CeO2‐TiO2 Hybid‐Nanotubes with Tunable Oxygen Vacancies as the Support to Confine Pt Nanoparticles for the Low‐Temperature Water‐Gas Shift Reaction. Issue 43 (16th November 2021) - Chen, Yaqian; Li, Xiangnan; Li, Juan; Du, Yubing; Peng, Quanming; Wu, Liangpeng; Xinjun,; Li,
Abstract: Reducible oxides as supports have been demonstrated to improve the activity of Pt catalysts towards water‐gas shift (WGS) reaction. The Pt species anchored by the oxygen vacancies derived from these supports play as catalytic sites during low‐temperature WGS reaction. Herein, we introduced CeO2 to modify TiO2 nanotubes (TiO2 NT) and prepared CeO2 ‐TiO2 hybid‐nanotubes ((CeO2 )x (TiO2 )1‐x NT, x=0.2, 0.4, 0.6) to confine Pt nanoparticles (NPs) as the efficient catalysts for the low‐temperature WGS reaction. Pt NPs confined in (CeO2 )x (TiO2 )1‐x NT catalysts exhibit higher WGS activity than that of the Pt NPs entrapped in pure TiO2 NT (Pt‐in‐TiO2 NT) and Pt/CeO2 catalysts throughout the entire reaction temperature range. Activity measurements coupled with the physicochemical characterization of catalysts suggest that the redox ability of PtOx species is positive correlated with WGS activity and oxygen vacancy adjacent to Pt (Pt‐Ov ) serves as the active site for H2 O dissociation and CO oxidation in WGS reaction. Abstract : CeO2 is introduced to tune the oxygen vacancies of TiO2 nanotubes as the supports to confine Pt catalysts. The sequentially enhanced activity of the catalyst of platinum nanoparticles confined in CeO2 ‐TiO2 hybid‐nanotubes ((CeO2 )x (TiO2 )1‐x NT, x=0.2, 0.4, 0.6) is attributed to anchor more numerous PtOx species with the higher redox ability, which plays the role in constructing the active Pt 0 ‐oxygen vacancy site for the water‐gas shift reaction.